1996
DOI: 10.1002/(sici)1096-9861(19960219)365:4<659::aid-cne11>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and columnar patterns of geniculocortical projections in the cat: Relationship to cytochrome oxidase

Abstract: We examined the laminar and columnar arrangement of projections from different layers of the lateral geniculate nucleus (LGN) to the visual cortex in the cat. In light of recent reports that cytochrome oxidase blobs (which in primates receive specific geniculate inputs) are also found in the visual cortex of cats, the relationship between cytochrome oxidase staining and geniculate inputs in this species was studied. Injections of wheat germ agglutinin-conjugated horseradish peroxidase were made into the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(13 citation statements)
references
References 80 publications
2
10
1
Order By: Relevance
“…In the cat, the relationship between the CO staining in the upper layers and the ocular dominance columns is unclear (Dyck and Cynader, 1993;Murphy et al, 1995;Boyd and Matsubara, 1996). In the squirrel monkey, we found no correspondence between the patches and the ocular dominance columns.…”
Section: Discussioncontrasting
confidence: 59%
“…In the cat, the relationship between the CO staining in the upper layers and the ocular dominance columns is unclear (Dyck and Cynader, 1993;Murphy et al, 1995;Boyd and Matsubara, 1996). In the squirrel monkey, we found no correspondence between the patches and the ocular dominance columns.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the area 18, but not the area 17, feedback pathway sends a stronger projection to layer A1 compared with layer A, whereas layer Cm appears to receive equally strong feedback from both ipsilateral and contralateral eye ocular dominance columns. Both of these characteristics recapitulate the patterns seen in the afferent pathways (Höllander and Vanegas, 1977;LeVay and Ferster, 1977;Geisert, 1980Geisert, , 1985Boyd and Matsubara, 1996). Finally, there is evidence that the Y-cell pathway to area 18 relays more heavily via the lower portion of each A layer (Bowling and Michael, 1984;Geisert, 1985), whereas the X-cell pathway to area 17 shows the opposite distribution.…”
Section: Laminar Distribution Of the Corticogeniculate Boutonssupporting
confidence: 53%
“…It has been suggested that a homologous population of cells might be subsumed within the neighboring ipsilateral eye laminae (Boyd and Matsubara, 1996); indeed, this is one possible explanation for the overrepresentation of layer A1 in the afferent pathway to area 18. Assuming that these cells would receive the same mixture of feedback that is characteristic to layer Cm, this might also explain the apparent anomalies in the pattern of input from area 18.…”
Section: Feedback To Magnocellular Layer Cmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 h of washing with 0.1 M PBS, the sections were incubated all day at room temperature and overnight at 4°C in fluorescein isothiocyanate (FITC)-or tetramethylrhodamine isothiocyanate (TRITC)-conjugated secondary antibodies. For histology experiments, wild-type (WT) and CHL1 Ϫ littermates were anesthetized and perfused and brains were processed for cytochrome oxidase (Boyd and Matsubara, 1996) or Nissl (Demyanenko et al, 1999).…”
Section: Methodsmentioning
confidence: 99%